Te Aroha o te Hauangiangi : Māori perspectives on healing from substance abuse : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Māori Studies at Te Pūtahi-ā-Toi School of Māori Studies, Massey University, Palmerston North, Aotearoa/New Zealand - Warbrick, Keremete Te Rangimaria (Massey University, 2006)
This thesis examines and describes Māori cultural components used in the treatment of substance abuse problems in the Taha Māori Programme at Queen Mary Hospital. This study explores themes that arise from the experiences of three therapists who worked in the Taha Māori Programme and eight clients who experienced cultural components in treatment. Together their personal narratives describe the healing journey from substance abuse. A Māori centred approach was used to guide the research process and a qualitative case study method was used to collate and analyse the data. Significant themes that emerged from the data were presented in a whakapapa paradigm that examined the healing journey from the realms of Te Korekore ki Te Pō ki Te Wheiao ki Te Ao Mārama.
Keywords: New Zealand; Substance abuse -- Treatment; Maori (New Zealand people) -- Substance use; Māori Masters Thesis